Pengaruh Work Life Balance Terhadap Optimalisasi Kinerja Karyawan Flight Operation PT. JAS pada Bandar Udara Internasional Soekarno-Hatta Tangerang, Banten - Amelia Romadhona Putri; Djoko Widagdo (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The density of flights at Soekarno-Hatta International Airport, Tangerang, Banten is the main factor causing work fatigue for employees. Especially at PT.JAS, the Flight Operation unit Load Control and Flight Coordinator often experience overtime which causes their Work Life Balance not to be met and has an impact on decreasing employee productivity. This study aims to determine the effect of Work Life Balance on optimizing the performance of Flight Operation employees at PT. JAS at Soekarno-Hatta International Airport, Tangerang, Banten. The data collection method used in this study is a quantitative method with a data collection technique in the form of a questionnaire distributed to 46 respondents, and also a Literature Study in the form of conducting a review of books, literature, and reports. The research methods used in this study are (Validity Test, Reliability Test, Classical Assumption Test Using the Normality Test Tested with the Shapiro Wilk Test, Simple Linear Regression Analysis, Correlation Coefficient Test, T Test, and also Determination Coefficient Test). The results obtained from this study are that Work Life Balance has an effect on the performance of employees of PT.JAS Flight Operation unit at Soekarno-Hatta International Airport Tangerang, Banten. This is proven by the T-test value, namely the calculated t value is greater than the t table, namely 10.889> 1.984 and the Determination Coefficient Test Results are also obtained at 0.729 or 72.9%, which means that the independent variable (Work Life Balance) has a significant effect on the dependent variable (Performance) by 72.9% and the remaining 27.1% is influenced by other factors not included in this study.